Analysis of swimming performance in FINA World Cup long-distance open water races - Zingg, M. A.; Rüst, C. A.; Rosemann, T.; Lepers, R.; Knechtle, B. (Extreme Physiology & Medicine, 2014)
Background: Age and peak performance in ultra-endurance athletes have been mainly investigated in long-distance runners and triathletes, but not for long-distance swimmers. The present study investigated the age and swimming performance of elite ultra-distance swimmers competing in the 5-, 10- and 25-km Fédération Internationale de Natation (FINA) World Cup swimming events. Methods: The associations of age and swimming speed in elite male and female swimmers competing in World Cup events of 5-, 10- and 25-km events from 2000 to 2012 were analysed using single and multi-level regression analyses. Results: During the studied period, the swimming speed of the annual top ten women decreased significantly from 4.94±0.20 to 4.77±0.09 km/h in 5 km and from 4.60±0.04 to 4.44±0.08 km/h in 25 km, while it significantly increased from 4.57±0.01 to 5.75±0.01 km/h in 10 km. For the annual top ten men, peak swimming speed decreased significantly from 5.42±0.04 to 5.39±0.02 km/h in 5 km, while it remained unchanged at 5.03±0.32 km/h in 10 km and at 4.94±0.35 km/h in 25 km. The age of peak swimming speed for the annual top ten women remained stable at 22.5±1.2 years in 5 km, at 23.4±0.9 years in 10 km and at 23.8±0.9 years in 25 km. For the annual top ten men, the age of peak swimming speed increased from 23.7±2.8 to 28.0±5.1 years in 10 km but remained stable at 24.8±1.0 years in 5 km and at 27.2±1.1 years in 25 km. Conclusion; Female long-distance swimmers competing in FINA World Cup races between 2000 and 2012 improved in 10 km but impaired in 5 and 25 km, whereas men only impaired in 5 km. The age of peak performance was younger in women (approximately 23 years) compared to men (about 25-27 years).